Using Work in Pairs Method to Improve Students’ Writing Skills in a University Level - Marsevani, Maya; Yeo, Frisca (Lingual Journal of Language and Culture; Vol 16 No 2 (2023): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2023.v16.i02.p06, 2023)
The method used was Classroom Action Research (CAR). By using this method, it might raise students' motivation in learning English especially to master language forms, structure and grammar. Most studies focused on improving students’ English skills in high school level. Hence, the researchers planned to implement work in pairs strategy to improve students’ writing skills. It focused on university students who had low motivation and lack of grammar while learning English, especially writing skills. Researchers formulated the research questions; How is work in pairs method be used to improve students’ writing skills? Pre-test and the post-test 2 had improved from lacking to fair. It was proved that implementing the pair work technique is a positive approach to boost students' writing skills, particularly in the context of descriptive writing. The average score of students increased, and the teaching-learning process improved significantly. Work in pairs method was useful in assisting students in writing descriptive text. The researchers hope by publishing this article, it will be useful for teacher and learners on learning English by using this work in pairs method